Association between Fine-needle Aspiration Cytological Features and CD4 Level in Human Immunodeficiency Virus-Associated Tuberculous Lymphadenitis Patients Admitted to Haji Adam Malik Hospital in 2017 - Delyuzar, Delyuzar; Sinulingga, Agri Borneos; Suryadi, Dedy (Open Access Macedonian Journal of Medical Sciences, 2019)
BACKGROUND: World Health Organization stated that one-third of the world’s population has tuberculosis with one infected person in every second. In 2015 there were 330,910 tuberculosis cases in Indonesia. This number increased compared to 2014, which amounted to 324,539 cases. HIV-positive patients with extrapulmonary tuberculosis accounted for 50% of TB cases, of which 35% were lymphadenitis. Lymph node fine-needle aspiration (FNA) is considered effective in determining the early diagnosis of lymphadenopathy. AIM: This study aims to evaluate the association between cytological features and CD4 level in HIV-associated tuberculous lymphadenitis patients in Haji Adam Malik Hospital in 2017. METHODS: This is an analytical study with a cross-sectional approach involving 42 samples. Cytological features were obtained by slide reviewed and CD4 level were obtained from the medical record. RESULTS: Analysis of the association of cytological features with CD4 level association revealed p-value of 0.353. CONCLUSION: This indicates that there is no significant association between FNA cytological features and CD4 level in HIV-associated tuberculous lymphadenitis patients.